2014
DOI: 10.1371/journal.pone.0084997
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting Active Users' Personality Based on Micro-Blogging Behaviors

Abstract: Because of its richness and availability, micro-blogging has become an ideal platform for conducting psychological research. In this paper, we proposed to predict active users' personality traits through micro-blogging behaviors. 547 Chinese active users of micro-blogging participated in this study. Their personality traits were measured by the Big Five Inventory, and digital records of micro-blogging behaviors were collected via web crawlers. After extracting 845 micro-blogging behavioral features, we first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 28 publications
3
87
2
Order By: Relevance
“…First, the personality characteristics extracted using other information such as thoughts and writings of people in the social networks (Qiu et al 2012;L. Li et al 2014) can be considered in finding the influential nodes.…”
Section: Resultsmentioning
confidence: 99%
“…First, the personality characteristics extracted using other information such as thoughts and writings of people in the social networks (Qiu et al 2012;L. Li et al 2014) can be considered in finding the influential nodes.…”
Section: Resultsmentioning
confidence: 99%
“…Because some Weibo users are inactive users, and thus not likely to share their attitudes on the internet, this study only focused on active users. In a previous research on Weibo (Li, Li, Hao, Guan, & Zhu, ), researchers found that the distribution of all individual users' total number of posts (136.65 ± 788.87) and average number of daily posts (2.84 ± 2.57). Therefore, in this study, active users were selected based on the following criteria: (a) at least 532 published Weibo posts (136.65 + 0.5 × 788.87 ≈ 532); (b) average number of daily posts ranged from 2.84 (the mean value of all individual users' average number of daily posts) to 40 (a threshold for excluding extreme users, like movie or sports stars, who might update Weibo posts for business purposes).…”
Section: Methodsmentioning
confidence: 96%
“…A personality prediction model trained by machine learning algorithms was used (L. Li et al, ). The training data of the prediction model was the posts from 547 active Chinese Sina Weibo users and their self‐rated personality assessed by 44‐item Big Five Inventory (BFI‐44).…”
Section: Methodsmentioning
confidence: 99%
“…We collected counselors' gender, therapeutic orientation, working time by crawling “Yi Psychology,” and computed their personality traits by ecological recognition technology. Then we used SPSS.19 to compare counselors' personality with the norm group, which were evaluated on the basis of one million microblog users' tweets (L. Li et al, ). We also explored the association of gender, therapeutic orientation, working time, and personality.…”
Section: Methodsmentioning
confidence: 99%